From green demand to deceptive practices: A cross-cultural study the impact of consumer green preferences on corporate greenwashing behavior in China, Republic of Korea, and Malaysia - Zhibin Tao (Sustainable Futures)
In the wave of globalization, the interaction between consumer green preferences and corporate greenwashing behavior is not only about business ethics and market integrity but also about the sustainable development of human society. However, research in this field is still in its infancy, particularly in terms of cross-cultural comparison. This study aims to delve into how consumer green preferences influence corporate greenwashing behavior, particularly within the three representative cross-cultural contexts of China, Republic of Korea, and Malaysia. The goal is to promote the healthy development of green consumption globally and contribute to building a future where humans and nature coexist harmoniously. Utilizing valid survey data from 1433 enterprises across these three countries, and employing SEM and fsQCA methods, the empirical test results indicate that among the three countries: (1) Consumer green preferences lead to corporate engagement in greenwashing behavior. (2) Consumer green preferences lead to market competitive pressure. (3) Market competitive pressure results in corporate greenwashing behavior. (4) Market competitive pressure plays a significant mediating role in the process by which consumer green preferences influence corporate greenwashing behavior. (5) Regulatory environment plays a moderating role in some of the impact paths across different countries, and in some impact paths, the moderating effect is absent. (6) The analysis results using the fsQCA method show that there are 4 different configurations leading to strong greenwashing behavior in enterprises in China, 3 in Republic of Korea, and 4 in Malaysia, and the most influential and explanatory configurations and paths have been identified. This study, with a global perspective, not only advances the theoretical innovation at the academic forefront of corporate governance and sustainability, but it also offers practical intelligent navigation for the strategic global layout of businesses. For policymakers, the findings of this research provide a solid theoretical foundation and forward-looking guidelines for constructing a green, fair, and sustainable market regulatory framework and governance system, holding significant value in guiding future research directions.